Exploring the relationship between maternal knowledge and age-appropriate vitamin A supplementation uptake in Nadowli-Kaleo District, Ghana, 2022 - Sorengmen Amos Ziema; Charles Alomatu; Edem Kojo Amedonu; Samson Obripuo (Journal of Interventional Epidemiology and Public Health)
Introduction: Children aged 6-59 months in Ghana and elsewhere receive vitamin A (VA) supplements routinely according to age schedules. Despite the health benefits, uptake among children remains unsatisfactory. Adequate maternal knowledge of VA supplementation (VAS) could help increase uptake. We explored the relationship between maternal knowledge of VAS and its age-appropriate uptake among children.